2016
DOI: 10.1111/dom.12711
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐dependent insulinotropic peptide secretion is induced by inflammatory stimuli in an interleukin‐1‐dependent manner in mice

Abstract: Recently, glucagon-like peptide-1 (GLP-1) levels have been found to be increased in response to inflammatory stimuli, leading to insulin secretion and prevention of hyperglycaemia during endotoxemia in mice. In the present study, we assess the relevance of the other incretin hormone, glucose-dependent insulinotropic peptide (GIP), as a regulator of glucose metabolism under inflammatory conditions. We found that lipopolysaccharide (LPS) increased GIP secretion in a time- and dose-dependent manner in C57BL/6J mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…We then focused on the possible involvement of enhanced inflammation in the adipose tissues of Lep ob/ob mice, as pro-inflammatory conditions in fat tissues were previously reported to contribute to insulin resistance and perturbation of glucose metabolism in Lep ob/ob mice [25,34]. Notably, in accord with our present study, the previous literature found that LPS induced GIP secretion [35]. They also showed that IL-1 signaling is required for the GIP secretion by LPS using IL-1R knockout mice.…”
Section: Discussionsupporting
confidence: 79%
“…We then focused on the possible involvement of enhanced inflammation in the adipose tissues of Lep ob/ob mice, as pro-inflammatory conditions in fat tissues were previously reported to contribute to insulin resistance and perturbation of glucose metabolism in Lep ob/ob mice [25,34]. Notably, in accord with our present study, the previous literature found that LPS induced GIP secretion [35]. They also showed that IL-1 signaling is required for the GIP secretion by LPS using IL-1R knockout mice.…”
Section: Discussionsupporting
confidence: 79%
“…Numerous studies have been reported an increase of GLP-1 secretion in human IBD patients and systemic plasma cytokines impact on intestinal hormone secretion. Many studies have shown that inflammatory cytokines accelerate GLP-1 secretion, while GIP secretion is stimulated with LPS and these secretions are mediated by the IL-1β-dependent pathway, but not IL-6 and TNFα [41]. Inflammatory stimuli are well known to be involved in intestinal hormone release, and we also observed high concentrations of plasma incretins as well as PYY (data not shown) in a GI-inflamed mouse model using DSS administration.…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore under physiological conditions GIP is secreted by intestinal K-cells [1] mainly following food intake. Since recent work demonstrated that GIP secretion can also be induced by inflammatory stimuli like IL-1, IL-6, and LPS independent from food intake [17] , [18] , we questioned whether the increase in GIP in our patient cohort was linked to inflammatory markers. However, we were unable to detect a significant association between GIP levels and the inflammatory markers CRP and WBC ( Supplemental Table 1 ), making this an unlikely explanation.…”
Section: Discussionmentioning
confidence: 98%